2010
DOI: 10.1186/1465-9921-11-122
|View full text |Cite
|
Sign up to set email alerts
|

Characterisation of COPD heterogeneity in the ECLIPSE cohort

Abstract: BackgroundChronic obstructive pulmonary disease (COPD) is a complex condition with pulmonary and extra-pulmonary manifestations. This study describes the heterogeneity of COPD in a large and well characterised and controlled COPD cohort (ECLIPSE).MethodsWe studied 2164 clinically stable COPD patients, 337 smokers with normal lung function and 245 never smokers. In these individuals, we measured clinical parameters, nutritional status, spirometry, exercise tolerance, and amount of emphysema by computed tomograp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

43
711
11
37

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 1,020 publications
(827 citation statements)
references
References 27 publications
43
711
11
37
Order By: Relevance
“…For example, there is a poor correspondence between somatic symptoms and objective disease severity in about 50% of asthma patients depending on the measure (Janssens et al, 2009). In chronic obstructive pulmonary disease (COPD), large scale studies on several thousands of patients showed large between-person variability in the relationship between objective airflow limitation (FEV1) and self-reported breathlessness, with a modest correlation overall (r = 0.36, Agusti et al, 2010;r = 0.28, Müllerová et al, 2014).…”
Section: How Different Are 'Explained' and 'Unexplained' Symptoms?mentioning
confidence: 99%
“…For example, there is a poor correspondence between somatic symptoms and objective disease severity in about 50% of asthma patients depending on the measure (Janssens et al, 2009). In chronic obstructive pulmonary disease (COPD), large scale studies on several thousands of patients showed large between-person variability in the relationship between objective airflow limitation (FEV1) and self-reported breathlessness, with a modest correlation overall (r = 0.36, Agusti et al, 2010;r = 0.28, Müllerová et al, 2014).…”
Section: How Different Are 'Explained' and 'Unexplained' Symptoms?mentioning
confidence: 99%
“…This is interesting because some previous analysis lasted only a few years. [5,7,19] According to our data, differences are found between our study groups with a cutoff of 6.2 years, which suggests that cohorts should have longer follow-ups if we wish to adequately establish the variability in FEV 1 decline. [20]…”
Section: Discussionmentioning
confidence: 89%
“…[4] However, more recent research is challenging this concept, since FEV 1 does not always decline, and this decline may vary,[5] as various rates of FEV 1 decline have been described depending on the severity of the disease,[6] and symptoms do not correlate with FEV 1 at the individual level. [7,8]…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…En el caso particular de las etapas GOLD y la disnea (MMRC), la difi cultad se explica porque en cada etapa GOLD la magnitud de la disnea es muy variable, como lo demuestra la Figura 5, y como ha sido recientemente destacado por otros 33 . Además, la AF no sólo depende de alguna característica fi siológica particular, sino también de aspectos psicosociales y ambientales (estado ocupacional, estado civil, presencia de depresión, entre otros).…”
Section: Discussionunclassified